2022
DOI: 10.3390/en15239217
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Heat Source System Degradation Due to Aging and Evaluation of Its Effect on Energy Consumption

Abstract: The performance of air conditioning systems deteriorate due to the natural aging and wear caused by operating the devices. This is termed “aging degradation,” and it results from a lack of appropriate maintenance which accelerates the degree of performance degradation. The performance degradation of an air conditioning system can cause problems such as increased energy consumption, deteriorated indoor heating environment, and shortened lifespan of air conditioning equipment. To prevent such problems, it is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Kim et al [25] designed survey items to assess business activities and energy consumption in hospital buildings as well as to develop an energy benchmark. Lee et al [26] conducted calculations to forecast the ideal maintenance intervals for airconditioning units. They found that the energy consumption of these units increased by approximately 41% in the 15th year compared to the initial energy consumption.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…Kim et al [25] designed survey items to assess business activities and energy consumption in hospital buildings as well as to develop an energy benchmark. Lee et al [26] conducted calculations to forecast the ideal maintenance intervals for airconditioning units. They found that the energy consumption of these units increased by approximately 41% in the 15th year compared to the initial energy consumption.…”
Section: The Literature Reviewmentioning
confidence: 99%